When languages die : the extinction of the world's languages and the erosion of human knowledge - Harrison, K. David (Oxford University Press, 2007)
In When Languages Die, K. David Harrison illustrates the individual face of language loss, as well as its global scale. Languages are the accretion of thousands of years of a peoples science and art - from observations of ecological patterns to creation myths. The author shows that the disappearance of a language is a loss not only for the community of speakers itself but also for our common human knowledge of mathematics, biology, geography, philosophy, agriculture, and linguistics. In this century, we face a massive erosion of the human knowledge base. The global abandonment of indigenous languages will bring a massive loss of accumulated knowledge and culture - this book argues for the irreplaceable nature of these unique knowledge systems and the urgency of documenting them before they are lost forever. Book jacket.